The Meaning of Togetherness in the Dynamics Of the Gemblongers Community Group - Winangsih, Rahmi; Mulyasih, Rahmi; Budiati, Ayuning; Hasuri, Hasuri; Mujtaba, Burhanudin (Future Science, 2025)
This research aims to examine the dynamics of communication in the Gemblongers community which plays a role in building harmonious togetherness among its members. The method used is a qualitative case study with a semi-structured interview approach, participatory observation, and document analysis to gain an in-depth understanding of the communication process and social interaction in the community. The results of the study show that communication between members runs openly and inclusively, with a strong cohesion strategy through routine activities, the use of social media as a means of disseminating information and strengthening social ties, as well as a constructive conflict handling mechanism. The SWOT analysis reveals the strength of the community in building strong emotional bonds and social networks, but it also faces challenges such as varied member participation and fundraising constraints. In conclusion, this study makes a theoretical contribution to the development of interpersonal communication theory in the context of heterogeneous social communities, as well as practical benefits as a reference in designing effective community empowerment and management programs. These findings are expected to strengthen the understanding of the importance of inclusive and collaborative communication in building harmonious togetherness in social communities.